A thriving agricultural sector in a changing climate: Meeting Malabo Declaration goals through climate-smart agriculture - De Pinto, Alessandro; Ulimwengu, John M. (International Food Policy Research Institute, 2017)
Given its heavy reliance on rainfed agriculture and projected climatic and weather changes, SSA faces multidimensional challenges in ensuring food and nutrition security as well as preserving its ecosystems. In this regard, climate-smart agriculture (CSA) can play an important role in addressing the interlinked challenges of food security and climate change.